NILAI SOSIAL BUDAYA DALAM DUWA GAPPI (BAKAR BATU) MASYARAKAT SUKU MEE DI PANIAI PAPUA TENGAH - Yonas Degei; Wigati Yektiningtyas; Kusdianto; Indah Selamet Budiarti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The Duwa Gappii (Stone Cooking) tradition of the Mee Tribe in Paniai Regency, Central Papua, is a cultural heritage that embodies significant social, cultural, and educational values. This tradition is not merely a traditional cooking method but also a symbol of unity, togetherness, mutual cooperation, gratitude, and respect for customs that have been passed down from generation to generation. During the process, stones are heated to a high temperature and then arranged in layers with leaves, tubers, vegetables, and meat until the food is cooked through heat transfer. This practice demonstrates the application of fundamental physics concepts, particularly heat transfer through conduction, convection, and radiation. Integrating the Duwa Gappii tradition into science (physics) education at the elementary school level provides students with opportunities to learn scientific concepts through experiences closely connected to their daily lives and cultural background. Learning based on local wisdom makes science instruction more contextual, engaging, and meaningful, thereby improving students' conceptual understanding while fostering pride in their cultural heritage. Furthermore, students are encouraged to develop critical thinking skills, observe scientific phenomena, and connect theoretical knowledge with real-life practices. The findings indicate that the Duwa Gappii tradition reflects strong values of mutual cooperation, teamwork, responsibility, diligence, social solidarity, and spirituality, expressed through prayers and acts of gratitude before the ceremony begins. The tradition also serves as a medium for transmitting cultural values to younger generations and strengthening the cultural identity of the Mee Tribe. Therefore, Duwa Gappii has considerable potential as a learning resource that integrates science, culture, and character education. Its implementation in modern education supports contextual learning while contributing to the preservation of local cultural heritage and the development of students' scientific literacy in the twenty-first century.